2014
DOI: 10.4236/jmmce.2014.22015
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Diffraction, Electron Paramagnetic Resonance and Optical Absorption Study of Bauxite

Abstract: The bauxite mineral obtained from Araku, Vishakapatnam district of Andhra Pradesh, India is used in the present work. Structural characterization was performed by X-ray diffraction (XRD). The mineral was found to be gibbsite in phase. The transitional metal ions present were investigated using electron paramagnetic resonance (EPR) and optical absorption spectra. The EPR results suggest that Fe 3+ has replaced Al 3+ in the unit cell of bauxite. The optical absorption spectrum is due to Fe 3+ which indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Th broad peak indicates the uniform distribution of the glass fibers within the epoxy matr and highlights the amorphous nature of the composite [21,30]. Generally, all the maj sharp peaks in the virgin specimen are due to the Gibbsite phase of the fire-retarda agent, alumina trihydrate [34]. Contrary to the EDS results, the peaks associated with al mina trihydrate disappeared from the burnt specimen XRD spectra irrespective of t presence or absence of oil contamination, suggesting the fire may have consumed the su face-level fire-retardant agent.…”
Section: Resultsmentioning
confidence: 95%
“…Th broad peak indicates the uniform distribution of the glass fibers within the epoxy matr and highlights the amorphous nature of the composite [21,30]. Generally, all the maj sharp peaks in the virgin specimen are due to the Gibbsite phase of the fire-retarda agent, alumina trihydrate [34]. Contrary to the EDS results, the peaks associated with al mina trihydrate disappeared from the burnt specimen XRD spectra irrespective of t presence or absence of oil contamination, suggesting the fire may have consumed the su face-level fire-retardant agent.…”
Section: Resultsmentioning
confidence: 95%
“…XRD diffractograms (Fig. 1b) of ATH nanoparticles, indicated that the ATHw particles had a mixed crystal phase of predominantly monocline gibbsite (Al(OH) 3 ) and meta-stable orthorhombic boehmite (aluminum oxide hydroxide, AlO(OH)) (Reddy et al 2014), being re ected in well-de ned narrow sharp peaks between 18° and 22° and some broader peaks at higher 2-theta (JCPDS No. 33 − 0018), respectively.…”
Section: Structural Morphological and Thermal Properties Of Synthesimentioning
confidence: 99%
“…The XRD diffractograms (Fig. 1c) indicated that the ATH particles had a mixed crystal phase of predominantly monocline gibbsite (Al(OH) 3 ) and metastable orthorhombic boehmite (AlO(OH)) (Reddy et al 2014), being reflected in the well-defined narrow sharp peaks between 18°and 22°and some broader peaks at higher 2-theta (JCPDS No. 33-0018), respectively.…”
Section: Structural Morphological and Thermal Properties Of Synthesized Nanoparticlesmentioning
confidence: 99%